Structural and Functional Analysis of Extracts in Plants - Lamponi, Stefania (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Structural and Functional Analysis of Extracts in Plants collects 1 editorial, 3 reviews, and 26 research articles reporting recent research findings which cover several aspects of plant-derived bioactive compounds, to correlate extraction techniques with the chemical composition of extracts and their bioactivity for identifying molecules that might be used as active substances in a wide variety of areas.This book is a valuable resource for members of the scientific community wishing to further explore plants and the therapeutic applications of their bioactive compounds. It will appeal to scholars, teachers and scientists involved in plant product research, and facilitate the development of innovative new drugs.